Risk Management Maturity Assessment at Central Banks - Denewet, Nicolas (IMF Working Papers; Working Paper ;, 2019)
Effective risk management at central banks is best enabled by a sound framework embedded throughout the organization that supports the design and execution of risk management activities. To evaluate the risk management practices at a central bank, the Safeguards Assessments Division of the IMF's Finance Department developed a tool that facilitates stocktaking of elements that are present and categorizes the function based on its maturity. Tailored recommendations are then provided to the central bank which provide a roadmap to advance the risk management function.